1984
DOI: 10.1002/food.19840280616
|View full text |Cite
|
Sign up to set email alerts
|

Einfluß der Ernährung auf die Darmflora

Abstract: In several groups of probands the influence of nutrition on the gut flora has been examined. In old people there is a striking decrease in the numbers of Bifidobacteria whereas those of Clostridium perfringens strongly increase and those of Enterobacteriaceae and Lactobacilli can be found somewhat higher than in the compared group. In a group of longevitial old aged men nourished with a fibre-rich diet these alterations are found less striking. Changing from a mixed Japanese diet to a "western diet" a tendenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In several studies, a Western diet (high in animal protein and fat, low in fiber) led to a marked decrease in numbers of total bacteria and beneficial Bifidobacterium and Eubacterium species [26, 29, 48]. Consumption of a Western diet has also been associated with production of cancer-promoting nitrosamines [123, 124].
Fig.
…”
Section: Diet and Microbiotamentioning
confidence: 99%
“…In several studies, a Western diet (high in animal protein and fat, low in fiber) led to a marked decrease in numbers of total bacteria and beneficial Bifidobacterium and Eubacterium species [26, 29, 48]. Consumption of a Western diet has also been associated with production of cancer-promoting nitrosamines [123, 124].
Fig.
…”
Section: Diet and Microbiotamentioning
confidence: 99%
“…There is accumulating evidence to support the notion that intestinal microbiota play a significant role in the maintenance of health. ( 3 5 ) Recent data from both epidemiological and clinical studies, suggests a relationship between intestinal microbiota and the onset of obesity and the metabolic syndrome. ( 5 ) The gut microbiota is composed of billions of bacteria and archaea.…”
Section: Introductionmentioning
confidence: 99%
“…There is accumulating evidence supporting the notion that intestinal microbiota plays a significant role in the maintenance of health. ( 1 3 ) Recent studies, both epidemiological and clinical, suggest a relationship between intestinal microbiota and the onset of obesity and metabolic syndromes. ( 4 ) Cani et al ( 5 ) showed that bacterial lipopolysaccharide (LPS) is a triggering factor for the onset of insulin resistance, obesity, diabetes, and metabolic endotoxemia.…”
Section: Introductionmentioning
confidence: 99%